Anlotinib Combined With Anti-PD-1 Antibodies Therapy in Patients With Advanced Refractory Solid Tumors: A Single-Center, Observational, Prospective Study - Yuan, Min; Zhu, Zhongzheng; Mao, Wei; Wang, Hui; Qian, Hong; Wu, Jianguo; Guo, Xianling; Xu, Qing (Frontiers in Oncology, 2021)
Introduction Anlotinib (AL3818) is a novel multi-target tyrosine kinase inhibitor (TKI) targeting vascular endothelial growth factor receptor (VEGFR) and suppressing tumor growth. Modulation of tumor suppressive immune microenvironment via the inhibition of vascular endothelial growth factor may augment the activity of immune checkpoint inhibitors. Here we described the results of safety, and clinical efficacy of anlotinib combined with immunotherapy in patients with advanced solid tumors, the serum cytokine levels, and peripheral blood T lymphocyte populations were detected simultaneously. Methods Twenty six cases with advanced late-stage cancers including lung, gallbladder, endometrial, gastric, pancreatic, penile cancers and melanoma were treated since January 2019. Patients received a combination of anlotinib (12mg) once daily on day 1 to day 14 (21 days as a course) plus anti-PD-1 antibodies every 3 weeks until progression or intolerable toxicity. Imaging was performed every 6 weeks for the first year of therapy. Blood samples were collected from patients prospectively. Serum interleukin (IL)-2, IL-4, IL-6, IL-10, Tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ) and circulating immune cell subsets were measured at baseline and after two cycles of treatment via flow cytometry. Results There were ten tumor types enrolled with lung, gallbladder, cholangiocarcinoma and soft tissue sarcoma being the most common. Most patients had received front line treatments for metastatic disease (80.8%). The objective response rate (ORR) was 23.1%, including one complete response (CR) (3.8%) and five partial responses (PR) (19.2%) and a disease control rate (DCR=CR+PR+SD) of 80.8% (21 of 26). The median PFS was 4.77 months (95% CI: 4.10-5.44 months). Three patients (11.5%) had grade 3 treatment-related adverse events. There were no grade 4 or 5 treatment-related adverse events. Grades 3 toxicities included hand-foot syndrome (n=2) and hypertension (n=1). Higher serum IL-2, IL-4, IL-10, TNF-α, IFN-γ levels and lower ratios of CD4/CD8 T cells were found in the responders compared with non-responders. Conclusions The preliminary data showed that the combination of anlotinib and anti-PD-1 antibodies demonstrated promising durable antitumor efficacy with acceptable toxicity in patients with various advance tumors, and promoted favorable changes in serum IL-2, IL-4, IL-10, TNF-α, IFN-γ levels and circulating immune cell subsets in clinical responders. It is worth to further validate the efficacy in a randomized prospective trial.